Safety compliance at the workplace: Employees at manufacturing small and medium enterprises (SMEs) in Kedah - Amnah, Sheikh Abdul Tawab Al-Ibyari (2017)
In 2016, the Malaysian government launched a total of 150 small and medium enterprise (SME) development programs with a total funding of RM 5 billion to assist more than 580 000 SMEs and their employees. With respect to long-term prospects, the SME Master Plan 2012 – 2020, apart from being intended to transform SMEs so as to achieve a high income nation status by 2020, is aimed to identify and facilitate the implementation of immediate actions to reduce the occupational death rate to 4.36/100, 000 workers and accident rate to 2.53/1000 workers, as well as to increase the quality of work poisoning to 30 percent through the enhancement of safety compliance at SMEs. The purpose of this study is to examine the positive relationships between (1) safety rules and procedures, (2) safety participation, (3) communication, (4) safety training, (5) management commitment, (6) work environment, and safety compliance. A cross-sectional study was conducted. Data was gathered through a questionnaire distributed to workers of the manufacturing sector of SMEs (n = 124). Data analysis was done using SPSS version 20.0. This study applied factor analysis, descriptive statistics, reliability analysis and inferential analysis to examine the relationships among the variables. Multiple regression results showed that the significant variables related to safety compliance are communication, safety training, and work environment and accounted for 63.6% of the total variance. The theoretical and managerial implications of the findings are discussed and the results of this study can be utilized by manufacturing SMEs, government agencies, general community, stakeholders, national social partners, and the general public to increase the efficiency and productivity of SMEs as well as competitiveness between organizations and employees to adopt a better quality of life as per standard OSH practices and effective safety compliance.